The Presence of Ford Madox Ford - Crankshaw, Edward; Stang, Sondra J.; Trevor, William (University of Pennsylvania Press, 2017)
To provide a fresh perspective--from new and unexpected points of view--Sondra Stang gathers together a number of distinguished writers and critics to prove Ford and his works. Among the many contributors commenting on Ford for the first time are C.H. Sisson, William H. Pritchard, Alison Lurie, Denis Donoghue, and William Gass. Included too are new poems by Richard Howard and Howard Nemerov and memoirs by friends, lovers, and family.